Musical and Non-Musical Factors Shaping Perceived Emotion in Popular Music: Educational Implications from a Scoping Review - Mutia Rahmi Zafirahana; Rita Milyartini (South Sulawesi Education Development (SSED), 2025)
This study maps the musical and non-musical factors shaping perceived emotion in popular music. Listeners’ emotional responses shape the appeal of popular music and its success in creative industries. Using a scoping review approach, articles were retrieved from SAGE Pub and Springer with the keywords “perceived emotion”, “music induced emotion”, and “popular music”. From 28,292 initial records, eight met the inclusion criteria. The analysis shows that musical elements such as groove, melody, tempo, and lyrics, together with non-musical aspects like memory, listener engagement, and cultural context, play significant roles in shaping perceived emotion. Beyond industrial applications, these findings also offer insights for music learning, suggesting that understanding perceived emotion may support educators in designing emotion-centered activities that foster students’ awareness, empathy, and reflective engagement with music.